Experimental Investigation Study into the Mechanical Properties of Autoclaved Aerated Concrete and Its Bond Material - Sarraa Dhiyaa; Ashraf Alfeehan (Journal of Engineering and Sustainable Development)
Most mechanical properties are often required for the design and linear or nonlinear modeling of masonry structures, as well as performance-based design. This article presents an experimental evaluation of the mechanical properties of autoclaved aerated concrete AAC masonry blocks and common bonding and plastering materials. The tests covered the most important mechanical properties of the materials, including density, ‎compressive strength, tensile strength, flexural strength, modulus of elasticity, Poisson's ratio, and shear bond. Samples of AAC blocks were prepared and tested, in addition to three typical materials utilized with these blocks: cement-sand, gypsum, and adhesive mortars. The shear bond test as triplet prisms was conducted to estimate the AAC block and bond material shear strengths. The results showed that cement-sand mortar was superior to other bonding materials in compressive strength. In contrast, the adhesive mortar showed higher tensile and shear strength values due to its special composition, which gives greater adhesive forces between different materials